Il wine business in un ambiente competitivo in cambiamento: scelte strategiche e finanziarie delle Pmi vitivinicole campane - Rossi, Matteo (Piccola Impresa / Small Business, 2013)
The aim of the paper is to analyze strategic choices and performance of Campania wine SMEs. In the last years the wine world was interested to a new competition and so Campania wine industry has showed structural weaknesses. However there are also firms with winning strategies and good performance